Application of lipidomics in bivalve aquaculture, a review - Vincenzo A. Laudicella; Phillip D. Whitfield; Stefano Carboni; Mary K. Doherty; Adam D. Hughes (Wiley Publishing Asia Pty Ltd, 2025)
Bivalve production is a relevant aquaculture activity in Europe; however, it is not developing with same extents of other aquaculture sectors due to causes connected with regulation stringency, labour cost, space availability, habitat loss as well as variability in recruitment events, climate change and diseases. Understanding the physiology and nutritional requirements of bivalves during aquaculture activities might result beneficial to fuel up the development of the sector. Lipids are important molecules as they are relevant components of cellular membranes acting in several physiological processes like reproduction, growth, immunological responses and energy reserve. Nevertheless, lipid diversity is still poorly understood despite the research efforts of the last decades. Technological advancements provide tools to unveil such diversity. Lipidomics, a branch of metabolomics, is the science targeting the lipidome (e.g. the totality of biological lipids in an organism). In this review, lipidomics, and its related concepts, are discussed providing an overview of recent lipidomics studies on bivalves. Lipidomics could result in several advantages if compared with traditional lipid profiling techniques; however, aims and scopes of future lipidomics studies should be expanded. Here, possible future applications of lipidomics in the context of bivalve production are presented and discussed. Unveiling the lipidome of marine bivalves could aid disclosing important information regarding nutrition, biology, physiology and epidemiology on bivalves. This knowledge, once applied, has the potential to improve bivalve production and the resilience of the sector to environmental changes.